Determining how the gestational changes, including low hemoglobin influence the HbA1c and estimated average glucose relationship - Ahmed, Humaira; Iqbal, Sahar Iqbal; same, Syed Talha Naeem; same, Fouzia Zeeshan Khan; same, Uzma Nusrat (International Journal of Pathology, 2024)
ABSTRACTBackground: Gestational Diabetes Mellitus (GDM) affects up to 14% of pregnancies globally, with accurate glycemic control critical for preventing adverse outcomes. While HbA1c is a standard marker for long-term glucose control, its reliability in pregnant women with anemia is debated. This study explores the association between anemia and glycemic indicators including Glycosylated hemoglobin (HbA1c), Random plasma glucose (rPG), and Estimated average glucose (eAG) in pregnant women with GDM. Additionally, it examined the correlation between average glucose levels or eAG, measured by random plasma glucose rPG, and HbA1C.Methods: A prospective case-control study was carried out over eight months at the Departments of Chemical Pathology and Obstetrics and Gynecology, Dow University of Health Sciences (DUHS). Pregnant women in their second trimester after being diagnosed for GDM through oral glucose tolerance test were classified into anemic (hemoglobin < 10.5 g/dL) and non-anemic groups. Blood samples were collected and analyzed for HbA1c, hemoglobin, and random plasma glucose levels. Data were processed using SPSS (version-26) different variables compared by using independent t-test and correlation analyses at a significance level of p < 0.05.Results: Mean values for eAG, HbA1C, and rPG were 174.22 ± 24.489 mg/dl, 8.342 ± 1.6152%, and 166.21 ± 21.478 mg/dl, respectively. Anemia was associated with significantly higher HbA1C (p < 0.001), eAG (p < 0.001), and rPG (p = 0.004). A strong positive correlation was observed between eAG and rPG (r = 0.958, p < 0.01), while eAG showed a moderate correlation with HbA1C (r = 0.501, p < 0.01). In contrast, the correlation between HbA1C and rPG was weaker (r = 0.331, p < 0.01).Conclusion: eAG proved to be a good indicator for assessing glycemic control in pregnant non-anemic women with GDM. Anemia significantly affected glycemic metrics, leading to higher HbA1C and glucose levels.